Imitating God and Familiar Identity: An Exploration in Developmental Psychology, Theology, and Ecclesial Identity Married Priests in the Catholic Church, Adam A. J. Deville (ed.), University of Notre Dame Press, 2021 (ISBN 978-0-268-20010-7), XXVI + 350 pp., pb 35 Made in the Image of God: Being Human in the Christian Tradition, Michael Fuller, and David Jasper (eds), Sacristy Press, 2021 (ISBN 978-1-78959-170-5), x + 282 pp., pb £24.99 Forming Resilient Children: The Role of Spiritual Formation for Healthy Development, Holly Catterton Allen, IVP, 2021 (ISBN 978-1-5140-0172-1), x + 190 pp., pb 24 - Farris, Joshua R. (Reviews in religion and theology, 2023)
The nature of familial identity is central to a growing number of theological works. The authors of the volumes here each represent a different set of issues, disciplines, and perspectives. The discussions, ironically, center around family. Made in the Image of God gives the readers a series of reflections on diverse theological topics oscillating around the image and identity. Forming Resilient Children is unlike Made in the Image of God in that it is not strictly speaking a theological reflection on diverse issues, but a work of developmental psychology focusing on the nature of the child and the familial context for the child. Married Priests in the Catholic Church offers the reader a series of ecclesial engagements on the topic of the vocation of priesthood as either married or celibate. Overlapping with the previous two volumes in content by touching on identity, the image of God, and the nature of creaturely relations to God, Married Priests is, in one sense, a sustained reflection on the meaning of familial and organic identity (as an image of God) to the Church.